2020
DOI: 10.2174/1568026620666200226104652
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy: Looking Back, Looking Forward

Abstract: Peptide receptor radionuclide therapy (PRRT) is a highly effective anti-cancer treatment modality for patients with non-resectable, metastasized neuroendocrine tumors (NETs). During PRRT, specific receptors that are overexpressed on the cancer cells are targeted with a peptide labeled with a DNA-damaging radionuclide. Even though PRRT is a powerful treatment for metastasized NET patients, the majority still cannot be cured at this stage of the disease. Hence, many investigators focus on improving the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…Many different angles for improvement of therapeutic efficacy are currently being investigated as NETs become more prevalent and standard of care treatment is still not curative 6 , 39 , 50 . As we have shown that SST 2 expression levels can influence cellular therapy effects, it is an interesting concept to stimulate SST 2 expression to improve therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Many different angles for improvement of therapeutic efficacy are currently being investigated as NETs become more prevalent and standard of care treatment is still not curative 6 , 39 , 50 . As we have shown that SST 2 expression levels can influence cellular therapy effects, it is an interesting concept to stimulate SST 2 expression to improve therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These features give important implications for our understanding of MRT radiobiology and future research directions. Apart from investigating different radionuclides, the current search for improvements includes testing other peptides or antibodies, identifying novel tumor target molecules and using combination treatments to enhance therapy effect [67]. Visualization of DNA damage induction patterns of beta-emitters, alpha-emitters and Auger electrons, ordered (from left to right) by decreasing penetration range and increasing complexity of induced DNA damage.…”
Section: Molecular Radionuclide Therapy (Mrt)mentioning
confidence: 99%
“…These features give important implications for our understanding of MRT radiobiology and future research directions. Apart from investigating different radionuclides, the current search for improvements includes testing other peptides or antibodies, identifying novel tumor target molecules and using combination treatments to enhance therapy effect [ 67 ].…”
Section: Dna Damage-inducing Therapiesmentioning
confidence: 99%
“…This emphasizes the need to further optimize [ 177 Lu]Lu-DOTA-TATE radionuclide therapy to further improve efficacy while reducing toxicity. This includes improved dosimetry hand in hand with a deep biological evaluation of superior radionuclides, improved SST 2 ligands, increased SST 2 levels, the role of tumor microenvironment, and combinations with immunotherapy, targeted therapy or DNA modulating agents, as well as predictive markers for improved patient selection and treatment follow-up [24,44,45,[89][90][91].…”
Section: Radiobiologymentioning
confidence: 99%